Spatial analysis of toxoplasmosis through EcoHealth approaches using GRA-1 recombinant: case in Sleman, Yogyakarta - Fihiruddin Fihiruddin; Barandi Sapta Widartono; Wayan Tunas Artama (Indonesian Journal of Biotechnology, 2020)
Toxoplasmosis is an obligate intracellular zoonotic parasite caused by Toxoplasma gondii that can infect all warm-blooded animals including humans. Prevalence of toxoplasmosis varies depending on climate, geography, and the presence of cats in an area. This study aimed to identify the prevalence and distribution of toxoplasmosis in Sleman, Yogyakarta through EcoHealth approaches. A total of  385 blood samples were collected from residents in the district of Sleman. Seven people from 55 villages were selected for blood sampling using a cluster method. The collected serums were tested by ELISA using recombinant Granule 1 protein (GRA-1) as  coated antigen. Data on altitude and coordinates of sampling sites were collected using GPS.  instruments, soil surface temperature in Sleman was obtained by satellite imagery, and cat population in residential areas was determined by questionnaire. The prevalence of toxoplasmosis in Sleman was 58%, of which distributed around rivers and in cattle pens. Based on altitude and temperature, toxoplasmosis cases were found the highest at 0-150 m (66.3%) and at temperatures of 26-30°C (66.4%). Areas with large numbers of cats had toxoplasmosis prevalence of 75.8% while areas with moderate and few cats were 56.5% and 49.0%, respectively. Thus, differences in the prevalence of toxoplasmosis at settlement were found based on altitude, soil surface temperature, and cat populations.